Intramolecular cascade annulation triggered by rhodium(III)-catalyzed sequential C(sp2)–H activation and C(sp3)–H amination - Song, Liangliang; Tian, Guilong; Van der Eycken, Johan; Van der Eycken, Erik V. (Beilstein Journal of Organic Chemistry, 2019)
A rhodium(III)-catalyzed intramolecular oxidative annulation of O-substituted N-hydroxyacrylamides for the construction of indolizinones via sequential C(sp2)–H activation and C(sp3)–H amination has been developed. This approach shows excellent functional-group tolerance. The synthesized scaffold forms the core of many natural products with pharmacological relevance.
Keywords: annulation; C–H activation; rhodium; acrylamide; heterocycles